Pemanfaatan Techno-Pest Control Berbasis IoT Untuk Membasmi Hama Padi di Area Persawahan Pondok Condongcatur - Dianna Ratnawati; Setuju; Zamroni; Sigit Purnomo; Moh Ahsan (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
Planthopper and grasshopper pests that attack rice plants in the Padukuhan Pondok rice fields, Condongcatur have an impact on decreasing productivity of rice farmers. The objectives of this community service are: (1) to produce an IoT-based techno-pest control device by utilizing solar cells as power supply; (2) increasing the skills of farmers in using efficient technology that is economical, modern and environmentally friendly. The methods used include experimentation, socialization and training. This community service activity is the manufacture of IoT-based techno-pest control tools and tool dissemination. The dissemination activity was successfully held and attended by 50 participants from the farmer's group of culinary sources, the participants actively asked questions and were enthusiastic in practicing the operation of the tools. 85% of participants can operate the equipment in groups. Techno-pest control tools can eradicate planthoppers and grasshoppers at a radius of 6m within 4 hours via 40kHz ultrasonic waves. This tool is integrated on the internet to monitor the situation of rice fields by accessing the website http://pkm.ptm.ustjogja.ac.id.